(untitled) (Research, Society and Development, 2024)
The aim of this study is to identify the epidemiological profile of SARS-CoV-2 infections in health professionals at a University Hospital in João Pessoa – Paraíba, Brazil. This is an epidemiological research, clinical-laboratory, descriptive and quantitative. The cases of infection were obtained through laboratory confirmation using the technique of polymerase chain reaction in real time reverse transcription (RT-qPCR) in samples of nasopharyngeal secretions (SNF) and data from the investigation form of suspected flu syndrome by the 2019 Coronavirus. A total of 67 participants perfomed the exam. Of these, only 18 (26.8%) showed viral detection for SARS-CoV-2 by RT-qPCR. The most affected gender was female 12 (67%). The median age was 42 years old. The most prevalent symptom was headache 14 (31.1%). There were no cases of comorbidity. Female health professionals over the age of 30 constituted the largest proportion of study participants.